2012
DOI: 10.1007/s00299-012-1327-8
|View full text |Cite
|
Sign up to set email alerts
|

5-Azacytidine combined with 2,4-D improves somatic embryogenesis of Acca sellowiana (O. Berg) Burret by means of changes in global DNA methylation levels

Abstract: 5-Azacytidine combined with 2,4-D increases the number of Acca sellowiana somatic embryos. Global DNA methylation is directly affected by these compounds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
45
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(52 citation statements)
references
References 44 publications
7
45
0
Order By: Relevance
“…In line with this postulate, we observed a significantly decreased level of 5 mC in the embryogenic culture of Arabidopsis and the reduction in the DNA methylation level has also been associated with SE induction in other plants (Santos and Fevereiro 2002;Xu et al 2004;Noceda et al 2009;Rodríguez-Sanz et al 2014;Teyssier et al 2014). However, in some plants, an increased (Fraga et al 2012;Rival et al 2013), differentially modulated (Leljak-Levanić et al 2004;Nic-Can et al 2013) and steady (Parra et al 2001) level of DNA methylation during SE has been reported. The diversity in the SE-associated DNA methylation levels suggests that various exo-and endogenous culture factors rather than the induction of embryonic development per se appear to contribute to the global DNA methylation level in cultured tissue (Huang et al 2012;Rival et al 2013;Li et al 2014;Rathore et al 2014).…”
Section: Se Induction Is Associated With the Decreased Level Of Globasupporting
confidence: 84%
See 2 more Smart Citations
“…In line with this postulate, we observed a significantly decreased level of 5 mC in the embryogenic culture of Arabidopsis and the reduction in the DNA methylation level has also been associated with SE induction in other plants (Santos and Fevereiro 2002;Xu et al 2004;Noceda et al 2009;Rodríguez-Sanz et al 2014;Teyssier et al 2014). However, in some plants, an increased (Fraga et al 2012;Rival et al 2013), differentially modulated (Leljak-Levanić et al 2004;Nic-Can et al 2013) and steady (Parra et al 2001) level of DNA methylation during SE has been reported. The diversity in the SE-associated DNA methylation levels suggests that various exo-and endogenous culture factors rather than the induction of embryonic development per se appear to contribute to the global DNA methylation level in cultured tissue (Huang et al 2012;Rival et al 2013;Li et al 2014;Rathore et al 2014).…”
Section: Se Induction Is Associated With the Decreased Level Of Globasupporting
confidence: 84%
“…Consistent with the diverse effects of 5-AzaC on gene expression level, the hypo-and hypermethylation of DNA in response to this chemical were reported in an embryogenic culture of Acca sellowiana, which were dependent on the plant genotype and the supplementation of the culture medium with 2,4-D (Fraga et al 2012).…”
Section: -Azac Treatment and Dna Methylase-related Mutations Affect supporting
confidence: 69%
See 1 more Smart Citation
“…Nucleic acids digestion procedures were based on the method described by Johnston et al (2005) and Fraga et al (2012). High performance liquid chromatography (HPLC) analysis was performed according to Johnston et al (2005).…”
Section: Plant Materialsmentioning
confidence: 99%
“…Application of 2,4-D in somatic embryogenesis had been reported on guava (Fraga et al 2012), chrysanthemum (Naing et al 2013), tagara herbal plant (Chen et al 2014a), and China rose (Chen et al 2014b); whereas picloram had been applied on pineapple (Roostika 2012), grapes (Dai et al 2015) and Ledebouria (Baskaran et al 2016). Nevertheless, application of 2,4-D to induce mangosteen somatic embryos resulted scarcely regenerated calli (Te-chato 1998; Rohani et al 2012).…”
Section: Introductionmentioning
confidence: 99%